Can flaxseed supplementation affect circulating adipokines in adults? An updated systematic review and meta-analysis of randomized controlled trials - Abbasi, Shaghayegh; Karimi, Kiana; Hossein Moridpour, Amir; Musazadeh, Vali; Faghfouri, Amir Hossein; Jozi, Hannane (Frontiers in Nutrition, 2023)
Findings of randomized controlled trials (RCTs) regarding the effect of flaxseed on adipokines concentrations are conflicting. Therefore, the present meta-analysis was conducted to provide definite and conclusive results. Systematically, Scopus, Embase, PubMed, Web of Science databases, and Google Scholar were searched for relevant literatures published up to December 2022. Based on random-effect models, standard mean differences (SMDs) were calculated for net changes in adipokines concentrations. Overall, 13 RCTs (15 arms) were eligible to be included.The results indicated that leptin was significantly reduced after the intervention with flaxseed supplement (SMD = -0.69, 95% CI: -1.37, -0.01; p = 0.048; I 2 =92.0%, p<0.001). Also, flaxseed supplements had no considerable effect on plasma adiponectin (SMD= 0.52, 95% CI: -0.20, 1.25, p = 0.159; I 2 =92.0%, p<0.001). Flaxseed significantly improves leptin but does not affect adiponectin concentrations. Additional future well-designed trials are required to further assess the potential benefits of flaxseed on adipokines in humans.